Integrating Telerehabilitation into the Prehabilitation and Rehabilitation Pathway in Colorectal Cancer: A Case Series - Jose Manuel Burgos-Bragado; Natalia Brandín-de la Cruz; Beatriz Carpallo-Porcar; Juan Luis Blas-Laina; Sandra Calvo; Carolina Jiménez-Sánchez (Reports)
Background and Clinical Significance: Colorectal cancer (CRC) remains a global health challenge with significant postoperative complications and functional declines. Telerehabilitation offers an accessible alternative to improve preoperative physical condition and postoperative recovery. Case Presentation: Five CRC patients scheduled for laparoscopic surgery participated in an asynchronous telerehabilitation multimodal program, including two weeks of prehabilitation and four weeks of postoperative rehabilitation. Delivered via a digital platform with remote physiotherapist support, the intervention improved functional capacity and muscle strength preoperatively, with partial recovery noted post-surgery. Conclusions: Integrating telerehabilitation into the CRC surgical pathway is feasible and may enhance functional outcomes and quality of life. Further studies are required to confirm these preliminary findings.